Panopticism of Normal Body Discourse in Advertisement - Sari Monik Agustin (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M) Institut Bisnis dan Komunikasi LSPR, 2018)
This writing aimed to identify panopticism of normal body discourse to advertisement audiences. In addition, this study also aimed to identify the truth game of the normal body discourse in the media. There are some key concepts used as frameworks, particularly Michel Foucault’s panopticism, discipline of bodies, power relations and discourse relations. It also used a framework of advertisement in critical perspectives and the philosophy of bodies to enrich the analysis. The paradigm of this writing was critical constructionism. This was a descriptive qualitative research and the data collection techniques were depth interviews with obese women based on BMI standards. This study identified Patriarchy Panopticism, a game of truth of normal body discourse, and the discourse of normal healthy body in media, especially in advertisement as the results. Patriarchy panopticism occurs when discourse and discipline resides invisibly, without coercion and productively maintain the discourse through self-surveillance. At the end, media is only a way to enlarge of Patriarchy Panopticism and used to perpetuate the ideology of patriarchy in the society.